Analisis Perhitungan Harga Pokok Produksi Dengan Metode Full Costing Sebagai Penentuan Harga Jual Bakso - Zurmansyah, Ee; Noviriani, Eliza; Azmiranti, Azmiranti (Indonesian Accounting Literacy Journal, 2025)
Micro, small, and medium enterprises often determine selling prices based on estimates or by following competitors' prices without considering all production costs. Therefore, the purpose of this study is to further investigate production costs at Kantin Maya so that researchers can provide suggestions and input. This is a quantitative study that uses descriptive methods to explain production cost calculations. This study uses the full costing method to determine selling prices based on field data. The cost-plus pricing method will be used to determine selling prices. Primary data from interviews and secondary data from daily expense records are used. The analysis results show that the full costing method yields higher production cost calculations compared to Kantin Maya. Additionally, Kantin Maya is advised to include all costs in production cost calculations and use the cost-plus pricing method with a full costing approach when determining selling prices, as the cost-plus pricing method is more advantageous than Kantin Maya's current approach. This is because the cost-plus pricing method with a full costing approach has proven to be more effective and profitable.